Role of Microbes and Nanomaterials in the Removal of Pesticides from Wastewater - Arpita Roy; Madhura Roy; Saad Alghamdi; Anas S. Dablool; Angham Ahmed Almakki; Ismat H. Ali; Krishna Kumar Yadav; Md. Rabiul Islam; Marina M. S. Cabral-Pinto (International Journal of Photoenergy)
Pesticides are a class of xenobiotic compounds that are recalcitrant and show persistence in the environment for a longer period of time. Research studies have linked their potential for mutagenicity, teratogenicity, and carcinogenicity. The accumulation of pesticides in water sources due to runoff from agricultural lands has posed a serious threat to the biota of the water ecosystem as well as to the human population. Long-term exposure to pesticides can cause neurological disorders, reproductive complications, cancer, immunological, and pulmonary diseases. The use of pesticides has dramatically surged in agricultural as well as nonagricultural practices. Tons of pesticides are applied in the fields, but a limited amount reaches to the target organism while the rest is wasted and gets accumulated in soil or ends up in water sources like groundwater or river, which results in eradication of nontarget organisms. A variety of pesticides are used for pest management, such as organochlorine (DDT), carbamates (carbaryl), organophosphates (malathion), and pyrethroids (pyrethrins). These chemicals are highly toxic to flora and fauna because of their nonbiodegradable and persistence nature. Biomagnification of pesticides usually leads to cause various problems in human beings. Organochlorines like DDT have been banned in many developed countries due to these reasons. Therefore, the removal of pesticides from wastewater and natural water sources is of utmost importance. Conventional methods possess various limitations; therefore, there is a requirement of an alternative method which can efficiently remove these pollutants from the wastewater. In this review, environmental impacts and health-related complications of pesticides and microbial remediation approaches and use of different nanomaterials in the pesticide removal have been discussed.